2008 7th IEEE/ACM International Symposium on Mixed and Augmented Reality 2008
DOI: 10.1109/ismar.2008.4637327
|View full text |Cite
|
Sign up to set email alerts
|

User evaluation of see-through vision for mobile outdoor augmented reality

Abstract: We have developed a system built on our mobile AR platform that provides users with see-through vision, allowing visualization of occluded objects textured with real-time video information. We present a user study that evaluates the user's ability to view this information and understand the appearance of an outdoor area occluded by a building while using a mobile AR computer. This understanding was compared against a second group of users who watched video footage of the same outdoor area on a regular computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Tsuda et al [2005] used five different techniques to visualize obscured information, including ground grids. Avery et al [2008] built a system to evaluate the see-through vision: outdoors; and in an improved version, Avery et al [2009] used multiple viewpoints to enhance the depth interpretation with "tunnel cut-out visualization" and edge overlay. In addition, Dey et al [2010] compared "Melt"-visualization to the X-ray with edge information of an occluding object and showed that Meltvisualization outperformed this alternative.…”
Section: Related Researchmentioning
confidence: 99%
“…Tsuda et al [2005] used five different techniques to visualize obscured information, including ground grids. Avery et al [2008] built a system to evaluate the see-through vision: outdoors; and in an improved version, Avery et al [2009] used multiple viewpoints to enhance the depth interpretation with "tunnel cut-out visualization" and edge overlay. In addition, Dey et al [2010] compared "Melt"-visualization to the X-ray with edge information of an occluding object and showed that Meltvisualization outperformed this alternative.…”
Section: Related Researchmentioning
confidence: 99%
“…8 Computercreated views of occluded items and locales appear in the user's vision of the situation. Our initial AR x-ray vision system employed wireframe models textured with video images captured from the outdoor environment.…”
Section: Distributive Vr/armentioning
confidence: 99%
“…Since smartphones have become widespread and its computing power has risen, applications have been developed for personal identification using sensors, GPS and AR (augmented reality) [4][5][6]. Several services, such as "Sekai camera [7]," "Layar [8]," display information that is derived from GPS data, and tags either printed on books or attached on objects using AR.…”
Section: Introduction mentioning
confidence: 99%